Perbandingan Metode Moora dan Metode Simple Additive Weighting (SAW) untuk Menentukan Pupuk Terbaik Pada Tanaman Kacang Panjang - Anmolliza; Zakir, Ahmad; Rafika, Arie (Jurnal TEFSIN ( Jurnal Teknik Informatika dan Sistem Informasi), 2023)
In Indonesia, many people consume nuts, the types of nuts consumed are long beans. One of the important factors that can affect the growth of long beans is to provide sufficient water and use the right fertilizer. In the Batang Kuis sub-district, especially in the village of Sugiharjo, many farmers still don't understand and don't know what type of fertilizer is right to use for long bean plants, because in the current era there are so many different kinds of fertilizer products, including chemical fertilizers. The method used in determining the best alternative fertilizer for long bean plants is the moora method and the Simple Additive Weighting (SAW) method as a comparison to determine the best fertilizer to be selected and used by farmers in fertilizing the long bean plants. The results of the comparison of the two methods, the Simple Additive Weighting (SAW) method is the result for the Npk Grower fertilizer alternative which gets the highest score as the best alternative fertilizer to be used for long bean plants.